PENGARUH STRES KERJA, BEBAN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA PERAWAT DI RUANG RAWAT INAP RSUD DATU BERU TAKENGON - Erma Elizar; Namora Lumongga Lubis; Yuniati Yuniati (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2020)
Nursing services greatly determine the quality of hospital services, but the services provided by nurses are still often complained of by the community. The highlight of nurse performance is a problem that must be addressed immediately. Performance in this case is closely related to how much workload, work stress and nurse motivation work in providing health services. Job stress is a common health problem and is often complained of by workers in various countries. The study design used quantitative analytical surveys with crossectional designs. The population of all nurses working in the Inpatient Room at Datu Beru Takengon Hospital was 304 people. The sampling technique uses Proportional Random Sampling. Data analysis was performed by univariate, bivariate and multivariate analysis with chi_square. The results obtained p-value = 0,000, 0,003, 0,000 <α 0,05, meaning that there is an influence between work stress, workload and job satisfaction on nurse performance, from the results of multivariate analysis found that the most influential variables in this study are load variables work with an Exp B value of 22.121 which means the workload is 22 times influencing the performance of nurses. Conclusions there is a relationship between work stress, workload and job satisfaction on nurse performance while multivariate analysis shows that the most dominant factor is the workload variable on nurse performance. It is recommended for nurses to use time more effectively in completing tasks that are burdened so that there is no accumulation of work so that it can be completed on time. Keywords : Job Stress, Workload and Job Satisfaction, Nurse Performance